2019
DOI: 10.3390/s19204454
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in Simultaneous hdEEG/fMRI Imaging: A Nonlinear Dimensionality Reduction Approach

Abstract: Simultaneous recordings of electroencephalogram (EEG) and functional magnetic resonance imaging (fMRI) are at the forefront of technologies of interest to physicians and scientists because they combine the benefits of both modalities—better time resolution (hdEEG) and space resolution (fMRI). However, EEG measurements in the scanner contain an electromagnetic field that is induced in leads as a result of gradient switching slight head movements and vibrations, and it is corrupted by changes in the measured pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…We found that there is significant residue from the cardioballistic artefact, and there are also remnants of electrooculographic and electromyographic artefacts. However, the found residues did not deviate from the standardly preprocessed recordings reported in [ 28 ]. In the future, it would be appropriate to consider the use of a methodology [ 28 ] to exclude detected clusters containing residues from further analysis of the EEG signal.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…We found that there is significant residue from the cardioballistic artefact, and there are also remnants of electrooculographic and electromyographic artefacts. However, the found residues did not deviate from the standardly preprocessed recordings reported in [ 28 ]. In the future, it would be appropriate to consider the use of a methodology [ 28 ] to exclude detected clusters containing residues from further analysis of the EEG signal.…”
Section: Discussionmentioning
confidence: 43%
“…To validate the EEG preprocessing pipeline, our unsupervised clustering algorithm introduced in [ 28 ] was applied directly to standardly preprocessed EEG data, and the resulting clusters were compared to those obtained from a large dataset also described in [ 28 ]. It was confirmed that no additional artefacts or unique clusters were found.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations